2013
DOI: 10.4236/ojmetal.2013.32a1002
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Enrichment and Accumulation of Heavy Metals in Soil and <i>Trigonella foenum-graecum</i> L. (Fenugreek) after Fertigation with Paper Mill Effluent

Abstract: The aim of the study was to investigate distribution, enrichment and accumulation of heavy metals in soil and Trigonella foenum-graecum (var. Pusa Early Bunching) after fertigation with paper mill effluent. Doses of paper mill effluent viz. 5%, 10%, 25%, 50%, 75% and 100% were used for fertigation of T. foenum-graecum along with bore well water (control). The results revealed that paper mill effluent had significant (P < 0.05) effect on EC, pH, OC, Na, Cd, Cr, Cu, Mn and Zn of the soil in both seasons. Insigni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…Further, the present investigation is in good agreement with the previous results obtained by Kiziloglu et al (2008) who described that wastewater irrigation increased soil salinity, exchangeable Ca and Mg ions. Singh (2007) proves that the significantly higher values of exchangeable cations have been reported in soils irrigated using paper mill effluent and also these results were similar to the values of Kumar and Chopra (2013); Kumar et al (2014) who reported that irrigation using wastewater leads to a significant increase in Ca and Mg in the soil as compared to groundwater or well water.…”
Section: S269supporting
confidence: 81%
See 1 more Smart Citation
“…Further, the present investigation is in good agreement with the previous results obtained by Kiziloglu et al (2008) who described that wastewater irrigation increased soil salinity, exchangeable Ca and Mg ions. Singh (2007) proves that the significantly higher values of exchangeable cations have been reported in soils irrigated using paper mill effluent and also these results were similar to the values of Kumar and Chopra (2013); Kumar et al (2014) who reported that irrigation using wastewater leads to a significant increase in Ca and Mg in the soil as compared to groundwater or well water.…”
Section: S269supporting
confidence: 81%
“…Hence the present investigation suggests the intake of samples devoid of chemical pollution as the samples collected from the rural vicinity satisfies the recommended dietary limit of intake of the essential minerals for a healthy balanced diet when compared with the samples collected from the urban vicinity. The results of the present investigation are by the findings of Kumar and Chopra (2013) who found that irrigation with wastewater significantly increased Cr in soil. These results are not consistent with Lu et al (2016) who revealed that the wastewater did not increase the Cr content of the soil.…”
Section: Nickelsupporting
confidence: 69%
“…The EC (1.96 ± 0.07 dS m -1 ) of the glass industry effluent contaminated soil was significantly (P < 0.01) increased to 125.28% when compared to groundwater irrigated soil. The increase in the EC of the effluent irrigated soil is likely due to the presence of more salts in the glass industry effluent [Kumar, V., et al 2013b]. Mohan et al 2007 concluded that the EC of water and wastewater is due to the presence of total dissolved solids.…”
Section: Effects Of Glass Industry Effluent Disposal On Soil Charactementioning
confidence: 99%
“…Toxic metals accumulate in the soil, which negatively affects plant growth and crop yield and even harms human health through enlarged food chain (Kumar et al 2013). Toxic metals are related to the behavior of plants in the soil and their bioavailability (Huang et al 2018).…”
Section: Grsp Functioning On Soil Toxic Elementsmentioning
confidence: 99%